1999
DOI: 10.1128/iai.67.11.5827-5833.1999
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Macrophage Resistance toPseudomonasExotoxin A Is Correlated with Decreased Expression of the Low-Density Lipoprotein Receptor-Related Protein

Abstract: Cellular intoxification by exotoxin A of Pseudomonas aeruginosa (PEA) begins when PEA binds to its cellular receptor, the low-density lipoprotein receptor-related protein (LRP). This receptor is particularly abundant on macrophages. We hypothesize here that inducible changes in cellular expression levels of the LRP represent an important mechanism by which macrophage susceptibility to PEA is regulated by the host. We have examined the effect of lipopolysaccharide (LPS) on LRP expression and PEA sensitivity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Pseudomonas Exo‐A has been previously characterized as using CD91 as its unique cellular endocytic receptor (32,33). Fibroblasts deficient in CD91 neither endocytose Exo‐A nor are they susceptible to Exo‐A‐mediated cell death (33); macrophage susceptibility to Exo‐A correlates with cellular CD91 expression, and toxicity is inhibited by the presence of CD91 agonists (41). If CD91 is the unique, or even predominant, cellular receptor for CRT, then we would hypothesize that cellular interactions with CRT would parallel those of Exo‐A.…”
Section: Resultsmentioning
confidence: 99%
“…Pseudomonas Exo‐A has been previously characterized as using CD91 as its unique cellular endocytic receptor (32,33). Fibroblasts deficient in CD91 neither endocytose Exo‐A nor are they susceptible to Exo‐A‐mediated cell death (33); macrophage susceptibility to Exo‐A correlates with cellular CD91 expression, and toxicity is inhibited by the presence of CD91 agonists (41). If CD91 is the unique, or even predominant, cellular receptor for CRT, then we would hypothesize that cellular interactions with CRT would parallel those of Exo‐A.…”
Section: Resultsmentioning
confidence: 99%
“…These toxins are important agents of human disease and are potential agents of bioterrorism (Balint, 1974;Boulton, 2003;Bradberry et al, 2003;Clarke, 2002;Dittmann et al, 2000;Franz & Zajtchuk, 2000;Lyczak et al, 2000;Madsen, 2001;O'Brien et al, 1992;Olsnes, 2004;Pickering et al, 1994;Tarr, 1995). Consequently, there is considerable interest in understanding how these toxins interact with host cells, with the ultimate goal of developing inhibitors of their action (Doring & Muller, 1989;Laithwaite et al, 1999;Ohmi et al, 1998;Sekino et al, 2004;Valdivieso-Garcia et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated the absence or reduce of LRP in different cell line, including LRP -/- embryonic fibroblasts, hepatoma and macrophage, were sufficient to protect cells from PEA intoxication [ 4 , 5 , 6 , 7 ]. These findings suggested that PEA might use LRP to gain entry into toxin-sensitive cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that the low-density lipoprotein receptor-related protein (LRP) functions as the receptor that PEA utilizes to gain access to mammalian cells [ 4 ]. In addition, the decreased expression of LRP may enhance macrophage and hepatocyte cell-line resistance to PEA induced cytotoxicity [ 5 , 6 ]. Laithwaite and collaborators reported that increased PEA sensitivity in BNL 1ME A7R.1 transformed hepatocytes was associated with increased functional cell surface LRP expression [ 7 ].…”
Section: Introductionmentioning
confidence: 99%